Aplicación del análisis de factor de correspondencia múltiple en un estudio de válvulas cardíacas en porcinos (2007)
ABSTRACT: The multiple correspondence factorial analyses is an extension of simple correspondence analysis for two set of characteristics. It permits the study of interdependence relationship between categorical or qualitative variables, that is, not metric. This model goes beyond the analysis of existing relationship between variables, because it allows knowing how this relationship is structured. This analysis has had a wide diffusion in different fields of research mainly in life sciences. The aim of this study was to apply this model to a previously reported study focused on the analysis of pig aortic valves entitled “Estudio anatomopatológico de válvulas aórticas porcinas a seleccionar para la elaboración de bioprótesis cardiacas”. By this model, it was possible to establish interrelationships between findings of macroscopic and microscopic lesions for two groups of aortic valves studied, with or without valve lesions. Of key relevance were the relationship found between endocardiosis-like degenerative lesions and vascular alterations like hemorrhage and congestion.